2013
DOI: 10.2109/jcersj2.121.880
|View full text |Cite
|
Sign up to set email alerts
|

Microwave dielectric properties of BaTi<sub>4</sub>O<sub>9</sub>–BaSm<sub>2</sub>Ti<sub>4</sub>O<sub>12</sub> composite ceramics

Abstract: BaTi 4 O 9 and BaSm 2 Ti 4 O 12 possess large dielectric performances and low dielectric loss, but their temperature-dependent properties could not meet with the practical use. In this paper, a composite ceramic system BaTi 4 O 9 /BaSm 2 Ti 4 O 12 (BaTi 4 O 9 + xSm 2 O 3 , x = 20, 40, 60, 80 mol %) was prepared and their dielectric properties was presented. The composite ceramic precursor were modeled by a cool iso-static press (CIP) and calcined at 1300°C for 6 h. The measured densities of ceramic samples inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…It has also been reported that the Fig. 4 Spots Atom (%) 3.02 (x = 0.4) ceramic at 1175°C. The degradation of the Q©f value can be attributed to abnormal grain growth at higher sintering temperatures, as shown in Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…It has also been reported that the Fig. 4 Spots Atom (%) 3.02 (x = 0.4) ceramic at 1175°C. The degradation of the Q©f value can be attributed to abnormal grain growth at higher sintering temperatures, as shown in Fig.…”
Section: Resultsmentioning
confidence: 70%
“…The temperature coefficient of resonant frequency, TCF, can be defined as follows: 3 (sintering at 1450°C) and obtained ultra low loss for microwave applications. The proposed dielectric has an extremely low loss, making it a very promising material for microwave and millimeter wave applications.…”
Section: Resultsmentioning
confidence: 99%
“…The EDX datum and data of corresponding spots AB were showed in Fig. 3(b) With increasing temperature, the bulk density increased to a maximum value of 3.66 g/cm 3 at 1175°C, and then it decreased. The reduction of density due to the abnormal grain growth is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 and then remilled for 12 h. A fine powder with 3 wt % of a 10% solution of polyvinyl alcohol (PVA 500, Showa, Japan) used as a binder was pressed into pellets, 11 mm in diameter and 5 mm thick, under a pressure of 200 MPa. The pellets were sintered at temperatures of 1100 1225°C for 4 h in air.…”
Section: Methodsmentioning
confidence: 99%
“…3 , which demonstrated an effective compensation in its¸f value. The resultant microwave dielectric properties were analyzed based upon the densification, the X-ray diffraction (XRD) patterns and the microstructures of the ceramics.…”
Section: )2)mentioning
confidence: 94%